Trianon hatása a Kárpát-medence régióinak fejlődésére - Gulyás, László (Közép-Európai Közlemények, 2010)
The regional development started at the beginning of 1900‟ years Hungarian Kingdom (which part of Austro-Hungarian Monarchy at this time). Regions have been formed, Budapest and another 10 towns became a regioncenters. The versaillan peace-system gave significant part of regions to other countries, or cut two parts with the borders. Because of it from 11 potential regioncenters 7 became the part of the new states. In my essay I proved that in Central-Europe the relation between the regional and the state has a major impact on development of the region. Development of the region depends on the economic policy of the certain state. There are mainly two possibilities: 1. The government economically utilizes the region. 2. The government develops the certain region. These had a detrimental impact on the development Carpathian-basin.